Sustainability of geothermal power plant combined with thermodynamic and silica scaling - Pambudi, Nugroho Agung; Itoi, Ryuichi; Jalilinasrabady, Saeid; Gurturk, Mert (Pergamon-Elsevier Science Ltd, 2018)
This method of combining thermodynamic and silica scaling analysis aims to improve efficiency, power output and sustainability in geothermal power plants which suffer from high concentration of silica. The proposed method was employed in an analysis of the Dieng geothermal power plant. The process starts with a performance evaluation of the existing power plant system, which is comprised of many components where losses of both energy and exergy occur. Once the performance of the existing plant has been evaluated, optimization of operating parameters can be applied to maximize its power output without the expensive addition of any new components. The process then continues with the development of scenarios with the power plant's design, seeking potential methods to improve its performance. In these scenarios, the plant is expanded into a double flash system, single flash-binary and double flash-binary. Silica scaling behavior models are then applied to determine which is the best scenario for development. It was found that a double flash system is the best expansion scenario for Dieng Geothermal Power Plant. This scenario produces a high power output of 29,155 kW and the lowest excess deposit of silica at 899 ppm. Although this scenario produces lower power output than the double flash -binary system, it has less negative impact from silica scaling. By introducing this system, the company can obtain additional power output of 4855 kW.
Keywords: Geothermal; Power plant; Single flash; Thermodynamic; Exergy analysis; Silica scaling